Pengaruh Pelatihan Kewirausahaan, Keterampilan Wirausaha dan Komitmen Individu Individual Terhadap Kinerja Pelaku UMKM Food & Beverage di Jember - Maharani, Bunga; Setyowati, Trias; Rahayu, Jekti (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to examine and analyze the influence of Entrepreneurship Training, Entrepreneurial Skills, and Individual Commitment on the Performance of Food & Beverage UMKM Actors in Jember. This study focuses on identifying the performance of UMKM operators. A quantitative approach is used, employing regression analysis to test the relationship between independent variables (Entrepreneurship Training, Entrepreneurial Skills, and Individual Commitment) and the dependent variable (Operator Performance). UMKM Food & Beverage operators in Jember were selected as the research subjects because they align with the research problem. Data was collected through a questionnaire (Google Form) distributed to Food & Beverage UMKM operators in Jember and will be analyzed using SPSS version 25. The research results indicate that Entrepreneurship Training positively and significantly influences Operator Performance with a calculated t-value of 6.410, which is greater than the critical t-value of 1.975 and a significance level of 0.000, which is less than 0.05. Entrepreneurial Skills also positively and significantly influence Performance with a calculated t-value of 8.974, which is greater than the critical t-value of 1.975 and a significance level of 0.000, which is less than 0.05. Commitment has a positive and significant effect on Performer Performance with a calculated t-value of 5.214, which is greater than the critical t-value of 1.975, and a significance level of 0.000, which is less than 0.05. Aside from the variables examined in this study, the results indicate that the three variables only account for 47.1% of the variance in MSME performance. This suggests that there are still 52.9% of other potential variables that may influence MSME performance, such as business motivation, market orientation, entrepreneurial competence, and individual characteristics. Therefore, future research is recommended to consider these factors in order to gain a more comprehensive understanding of MSME performance.